ANALYSIS OF TRANSFER OF SHORT STORY “ROBOHNYA SURAU OUR” BY A.A. NAVIS INTO A DRAMA SCRIPT AND ITS IMPLICATIONS ON LEARNING IN HIGH SCHOOL - Harahap , Andi Syahputra (LUMBUNG AKSARA, 2025)
This research is motivated by the lack of students' understanding of the media transfer in Indonesian language learning, as well as the limited use of media/teaching materials. This study aims to describe the process of transferring the media of the short story "Robohnya Surau Kami" by A.A. Navis into a drama script, then describe the implications of changing the form of the short story into a drama script for literature learning in high school. The method used in this study is qualitative descriptive research. The results of this study show that the changes in the media transfer of the short story "Robohnya Surau Kami" by A.A. Navis into a drama script have undergone changes in the form of additional dialogue, sampiran text, characters, and situations. Changes in the form of reducing dialogue and situations. Then changes in the form of changes in variations, namely characters and situations. And show teaching materials and teaching materials for teacher references in providing students with an understanding of the media transfer.